The anti-inflammation and skin-moisturizing effects of Boehmeria tricuspis-mediated biosynthesized gold nanoparticles in human keratinocytes - Tran, Thi Hoa My; Wang, Rongbo; Kim, Hoon; Kim, Yeon-Ju (Frontiers in Pharmacology, 2023)
Introduction: Recently, nanotechnology has emerged as a potential technique for skin generation, which has several treatment advantages, such as decreased drug cytotoxicity and enhanced skin penetration. Boehmeria tricuspis (BT) belongs to the Urticaceae family and is rich in phenolic and flavonoid compounds. In this study, we biosynthesized gold nanoparticles (BT-AuNPs) using BT extract to explore their anti-inflammatory and skin-moisturizing properties in keratinocytes. Methods: Field-emission transmission electron microscopy, energydispersive X-ray spectrometry, dynamic light scattering, and Fourier-transforminfrared spectroscopy were used to examine the synthesized BT-AuNPs. qRT-PCR, western blot, and ELISA were applied for investigating the effect of BT-AuNPs on anti-inflammation and moisturizing activity in HaCaT cells. Results: At concentrations below 200 μg/mL, BT-AuNPs had no cytotoxic effect on keratinocytes. BT-AuNPs dramatically alleviated the expression and secretion of inflammatory chemokines/cytokine, such as IL-6, IL-8, TARC, CTACK, and RANTES in keratinocytes stimulated by tumor necrosis factor-α/interferon-γ (T + I). These anti-inflammatory properties of BT-AuNPs were regulated by inhibiting the NF-κB and MAPKs signaling pathways. Furthermore, BT-AuNPs greatly promoted hyaluronic acid (HA) production by enhancing the expression of hyaluronic acid synthase genes (HAS1, HAS2, and HAS3) and suppressing the expression of hyaluronidase genes (HYAL1 and HYAL2) in HaCaT cells. Discussion: These results suggest that BT-AuNPs can be used as a promising therapeutic alternative for treating skin inflammation. Our findings provide a potential platform for the use of BT-AuNPs as candidates for treating inflammatory skin diseases and promoting skin health.